The linguosemiotic vector in Russian as a foreign language textbook series “Getting to know Modern China” - Lidiia G. Zolotykh; Svetlana I. Elnikova; Olga Yu. Kosmacheva (Russian Language Studies)
The relevance of this study is determined by two factors. First, the vectors of the new mission of higher foreign language education in China for training qualified Russianspeaking specialists have not been studied in general, at the scientific and methodological level. Secondly, there are no studies on the ideological significance of the linguosemiotic vector ‘Chinese’ for Chinese students in Russian linguistics. The aim of the study is to identify the fundamental linguosemiotic elements of the socialist system of the new era with Chinese characteristics as a vector for developing the ability to interpret Chinese practice and theory in Russian. The research is based on four Russian as a Foreign Language textbooks from the series “Getting to Know Modern China” (2022), which are based on Xi Jinping’s ideas on socialism with Chinese characteristics for the new era. The main research methods are linguosemiotic analysis and statistical methods. The study describes the linguodidactic model of the analyzed textbooks, evaluates the optimal integration of ideological and political concepts into educational programs for reinforcing basic Russian as a Foreign Language skills in Chinese universities, and identifies the specific use of the component ‘with Chinese characteristics’ in the textbook series. The findings are supported by statistical analysis of the micro-language within the study material, confirming the predominance of ideologemes with the component ‘Chinese’ as a linguosemiotic element structuring the linguodidactic foundation of the textbooks. The frequency analysis of the comprehensive component ‘with Chinese characteristics’ reveals its value-based features as a structural-semantic element of linguistic units in various formats, facilitating the acquisition of macro- and micro-text strategies. This study refines the understanding of the linguistic personality of Chinese students, updates methodological approaches to their education, and considers the discourse system with Chinese characteristics and the development of intercultural communication skills.